DAMPAK PEMEKARAN DESA TERHADAP KESATUAN HUKUM ADAT (STUDI KASUS PEMEKARAN DESA SIBIRUANG MENJADI DESA BANDUR PICAK KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR) - Helmi, Ahmad Zuhdi; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Governance Management mounted by Countryside of Bandur Picak of District of Koto of Pate;Upstream Camphor generate various polemic in management of countryside governance, specially Countryside of Bandur Picak, where countryside management during the time namely countryside of mains of Countryside Sibiruang cannot be locked out of a concept " String of Bapilin Tigo or Tigo of Stove Sajarangan" with the meaning activity management in countryside very relate to the institute of exist in countryside namely, Countryside Governance, Ninik Mamak (leader of tribes) and Moslem intelectual. Target of research is to know and explain the impact of pemekaran countryside to unity of Customary Law in Countryside of Sibiruang and Countryside of Bandur Picak of District of Koto of Pate;Upstream Camphor, and description of about effort is solving of the problem of unity customary law in Countryside of Sibiruang and Countryside of Bandur Picak of District of Koto of Pate;Upstream Camphor. Analyse the data of performed within this research is data analysis qualitative. Affect the breaking countryside to unity of Customary Law in Countryside of Sibiruang and Countryside of Bandur Picak of District of knowable Koto Pate;Upstream Camphor namely, Breaking of Countryside of Countryside of Bandur Picak of District of Koto of Pate;Upstream Camphor from its mains countryside is Countryside Sibiruang generate the polemic in execution of values and unity [of] customary law of exist in both the countryside. Both the countryside difficult cut loose from customary law unity is woke up by since of old. Before formed by Countryside of Bandur Picak of District of Koto of Pate;Upstream Camphor, unity of customary law well-held orderlyly is fluent without existence of various problem that happened. But after happened by the break, unity of customary law still coalesce namely Custom Sprout in Countryside of Bandur Picak of District of Koto of Pate;Upstream Camphor, while sprout Syara' (religion) in Countryside Sibiruang. Keyword : Village Expansion, Regional Autonomy, and Common Law